Ophthalmology residency training in India: Comparing feedback about how the training equips ophthalmologists to combat retinal diseases. READS report #6 - Gogate, Parikshit (Indian J Ophthalmol, 2019)
PURPOSE: To document whether the residency training in management of retinal diseases has improved in 2000s to meet the increasing demand of retina care in India. METHODS: A survey, using a prevalidated questionnaire, was conducted by Academic and Research Committee (ARC) of the All India Ophthalmological Society (AIOS) in 2014–2016 among ophthalmologists to document teaching of retina-related clinical and surgical skills in the postgraduate residency program. RESULTS: The 144-item questionnaire was mailed to 4512 practicing ophthalmologists with residency training in two different periods, between 1967 and 2000 (group 1; 20(th)-century trained) and between 2003 and 2012 (group 2; 21(st)-century trained). Response was received from 320 (19.1%) of group 1 ophthalmologists and 531 (18.7%) of group 2 ophthalmologists. The average age was 49.2 ± 8.7 and 32.6 ± 4 years, respectively. Group 2 residents had received superior training in indirect ophthalmoscopy, slit lamp biomicroscopy using + 78 and + 90D lens, optical coherence tomography, fundus photography, and fluorescein angiography (all P < 0.001), but there was large variation between the training institutions. The residents were not taught vitreous and retinal detachment surgeries in either period of training. CONCLUSION: Teaching of retina-related clinical skills have improved in Indian residency program, but there are variations across programs. This information might help redesign the ophthalmology residency programs to meet the demands of comprehensive eye care and universal health coverage of increasing retinal diseases in India.